Net Neutrality and Internet Fragmentation: The Role of Online Advertising - Anna D'Annunzio; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate the relation between Net Neutrality regulation and Internet fragmentation. We model a two-sided market, where Content Providers (CPs) and consumers interact through Internet Service Providers (ISPs), and CPs sell consumers' attention to advertisers. Under Net Neutrality, a zero-price rule is enforced. By contrast, in the Unregulated Regime, ISPs make access to their subscribers for CPs conditional on payment of a termination fee. Multiple impressions of an ad on the same consumer are partially wasteful. Thus, equilibrium ad rates decrease when audiences overlap. We show that ISPs may strategically set termination fees to induce fragmentation. This takes place when advertising revenues are potentially large but strongly diminished by competition among CPs, and when consumers are not highly sensitive to content availability. We therefore identify an important link between termination fees, the online advertising market and Internet fragmentation. We extend the model to account for multi-homing consumers, vertically integrated ISPs, third-party advertising platforms and heterogeneous CPs.
Keywords: L10; D43; L13; L51; 330; net neutrality; two-sided markets; internet; advertising; fragmentation